2019
DOI: 10.1109/tnsre.2019.2935242
|View full text |Cite
|
Sign up to set email alerts
|

Handrail Holding During Treadmill Walking Reduces Locomotor Learning in Able-Bodied Persons

Abstract: Treadmills used for gait training in clinical rehabilitation and experimental settings are commonly fitted with handrails to assist or support persons in locomotor tasks. However, the effects of balance support through handrail holding on locomotor learning are unknown. Locomotor learning can be studied on split-belt treadmills, where participants walk on two parallel belts with asymmetric left and right belt speeds, to which they adapt their stepping pattern within a few minutes. The aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Handrails were detached to omit grasping reactions as this reduces the effects of perturbations and affects motor learning (Buurke et al, 2019). A full-body harness connected with a rope to an overhead frame allowed the participants to move freely without body weight support, but prevented them from hitting the treadmill in case of falling.…”
Section: Methodsmentioning
confidence: 99%
“…Handrails were detached to omit grasping reactions as this reduces the effects of perturbations and affects motor learning (Buurke et al, 2019). A full-body harness connected with a rope to an overhead frame allowed the participants to move freely without body weight support, but prevented them from hitting the treadmill in case of falling.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were not made aware of their particular training condition and were asked not to look down at the belts. Handrail use while training was discouraged to maximize motor learning (30), and participants wore a harness for safety without body weight support. Feedback was restricted to mentioning if foot placement was likely to cross the midline, and regarding the amount of time remaining in the training block.…”
Section: Design and Interventionmentioning
confidence: 99%
“…Therefore, during session II, the individuals may have adapted to their new baseline values. The higher asymmetry may also be explained by the hypothesis that in this study, the participants held onto a safety handrail throughout the adaptation phase where, as in the past study, they did not do so, and holding onto a safety handrail has been found to affect the response of participants in split-belt treadmill training [ 80 , 81 ]. The application of the proposed exponential models also revealed that there was an overshoot in the symmetry series from the adaptation phase in session II.…”
Section: Discussionmentioning
confidence: 91%